Konsep shāliḥ dalam al-Qur’an (Analisis Tematik atas Tafsir al-Qurṭubī) - Imamurrizal, M. Abda’; Ahmad Mustofa; Ahmad Saifudin (Rayah Al-Islam, 2025)
The concept of shāliḥ in the Qur’an is often narrowly interpreted as individual spiritual piety, while in fact it encompasses broader social and leadership dimensions. Such a partial understanding may lead to the neglect of social responsibility and moral leadership in Muslim society. This study aims to: (1) examine the linguistic meaning of the term shāliḥ in the Qur’an; (2) analyze how al-Qurṭubī interprets verses containing the term; and (3) explore its relevance in individual, social, and leadership contexts. This research uses a qualitative approach through library research and applies thematic interpretation (tafsīr mawḍū‘ī). The findings indicate that al-Qurṭubī views shāliḥ as an integrative concept that connects ritual devotion, social responsibility, and ethical leadership. The study implies that the understanding of piety should be expanded beyond ritual obedience toward contributing to social justice. This perspective is relevant to Islamic education, public preaching, and social policy to foster a more holistic vision of piety in contemporary Muslim societies.